Development of Teaching Material Models of English Courses Based on Local Wisdom to Improve Skills of PGSD Students of English Texts - Yon Adlis (Budapest International Research and Critics University, 2022)
This study aims to develop a model of teaching materials for English courses based on local wisdom to improve the skills of PGSD students in understanding English texts. This research was conducted by adopting a design and development that refers to the theory of Borg and Gall with the steps of implementing the research as follows: (1) research and data collection; (2) develop a research plan, formulate a model of teaching materials (3) develop a product draft; (4) initial field trials; (5) revise the results of the trial; (6) field trials; (7) revision of the results of field trials; (8) field implementation test; (9) final product refinement); implementation of the model of teaching materials. The subjects of this study were 38 students who were taking English courses at the Elementary School Teacher Education Study Program. The results of data analysis show that (1) teaching materials for English courses, especially reading comprehension, have not been prepared based on local culture, (2) questions/questions/assignments/practices that follow reading comprehension teaching materials have not been able to improve students' ability to communicate in English, ( 3) students need teaching materials for English courses, especially reading comprehension based on local culture and which can improve communication skills in English and Jambi Malay cultural literacy, (4) assessments of experts and practitioners show that this supplementary reading material is seen as from content, appearance, questions/tasks/practices,/questions according to student needs,and (5) this supplementary reading material model is effective in improving students' skills in understanding the contents of reading texts in English, especially understanding the reading texts.